TIAA-CREF. (B), Organizing around the customer - from managing assets to managing relationships - Rosenthal, Jean W., 1945- (SAGE knowledge. Cases., 2016)
By the end of his first year as CEO, President and Chairman, Herb Allison had initiated a transformation at TIAA-CREF (Teachers Insurance and Annuity Association-College Retirement Equities Fund). This case examines the self-evaluation process which allowed the company to review its relationships with its customers and redefine its goals and its culture.